A feminist critique of the prostitution/sex work debate: recommendations for legislative change in South Africa - Levick, Margaret Susan (Centre for Law and Society, 2024)
The fact that the exchange of sexual acts for money no longer solely goes by the name 'prostitution', but is now also being referred to as 'sex work', suggests there is a new body of thought tackling the old perceptions and levels of acceptability that the industry has experienced in the past. The movement towards the acceptance of prostitution as just another legitimate commercial activity is not however without controversy. There remains a complex array of opinion, not least within the Feminist Movement, continually raising sensitive questions about particular core values lying at the heart of the debate. Yet the ideological battlefield which characterizes prostitution does not end with the intellectual sparring of interest groups. It is both a practical and a public interest issue which affects health, welfare and labour policies, municipal zoning and critically, the lifestyles of sex workers themselves. In the past, Cape and Durban city councillors have called for the legalisation of prostitution in South Africa (Argus 2/4/93; 3/4/93; 5/4/93, Cape Times 31/3/93). These calls however came at a time when there was a fairly long history of prohibitive legislative precedent supported by the Christian National Government and coupled with a lack of recourse to a Bill of Rights. Subsequently there has been a call for decriminalisation by the National Women's Coalition - which represents more than eighty women's groups - but the current Minister of Justice, Dullah Omar, has said that the issue would be addressed at "a later stage" (Cape Times 21/5/94). Suggestions for change, such as 'those called for by the Cape Town and Durban city councillors, have almost exclusively focused upon public interest issues without responding to the dangers and abuse that those involved in the profession experience. As an illegal and 'outsider' group to the rest of society, sex workers have not had adequate recourse to the law and this has added to their vulnerability.